Phyllanthus balakrishnanii sp. nov. (Phyllanthaceae), an interesting discovery from the southern Western Ghats, India - Sunil, Chandrasseril Narayanan; Prabhukumar, Konickal Mambetta; Kumar, Vannaratta Veettil Naveen; Thomas, Valukattil Ponnachan; Bhavadas, Narayanan; Balachandran, Indira (Phytotaxa, 2016)
A new species of Phyllanthus (Phyllanthaceae), P. balakrishnanii, from the southern part of the Western Ghats, India, is described and illustrated. A detailed description and data on distribution and phenology are provided along with colour photographs, and its affinities with allied taxa are discussed.